2019
DOI: 10.1002/2050-7038.12148
|View full text |Cite
|
Sign up to set email alerts
|

Fuse saving scheme in highly photovoltaic‐integrated distribution networks

Abstract: Summary The high penetration level of photovoltaic (PV) units increases their injected fault current that it may result in fuse‐recloser miscoordination in distribution networks. The conventional coordination techniques are based on shifting the fast operation curve of the recloser below the characteristic curve of the fuse for fuse saving in the case of a temporary fault. However, these techniques save fuse if the slopes of fuse and recloser characteristic curves are same. Also, in the case of the high penetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
(88 reference statements)
0
11
0
Order By: Relevance
“…Analysing Figs. 14 and 15, it can be concluded that the increase of the DER penetration level by increasing the active power supplied by the photovoltaic panels or by connecting more DER units to the distribution system reduces the short‐circuit current contribution of the main network (node 1) [32]. Therefore, it is important to mention that the load and short‐circuit current variation, shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Analysing Figs. 14 and 15, it can be concluded that the increase of the DER penetration level by increasing the active power supplied by the photovoltaic panels or by connecting more DER units to the distribution system reduces the short‐circuit current contribution of the main network (node 1) [32]. Therefore, it is important to mention that the load and short‐circuit current variation, shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The components of microgrid are shown in Figure 1. 77 A simplified microgrid system is equipped with (a) controllable generation like diesel generators and load bank, (b) not controllable generators (limited) like the photovoltaic cell 78,79 and wind turbine, 80,81 and (c) distributed energy storage like batteries and super-capacitors is schemed in Figure 2.…”
Section: Microgrid Structure and Operationmentioning
confidence: 99%
“…Installation of DGs in the distribution networks, owing to their fault current contribution, can cause fuse-saving failure and maloperation issue for the recloser-fuse protection [14]. To overcome the fuse-saving challenge, a recloser-fuse protection classification technique in [15], a voltage-assisted protection scheme in [16], an adaptive reclosing scheme by [17], communicationfree adaptive current limitation approaches by [18,19], and another fuse-saving scheme for DC MGs in [20] are developed. MG protection should be confined to inexpensive schemes.…”
Section: Introductionmentioning
confidence: 99%